Pertanggungjawaban Pidana Pelaku Turut Serta Melakukan Pemerasan Dengan Ancaman Berdasarkan Putusan Nomor 672/PID.B/2020/PN.Tjk - Zainab Ompu Jainah; Anggalana Anggalana; Erlina B; Desta Fani Acbel; Sigit Pamungkas (Wajah Hukum, 2021)
Extortion and threats are an act against the law and the perpetrator is obliged to take responsibility for his actions as regulated in the Extortion Law with Threats is a complaint offense so that the authorities can act if there is a complaint and the victim of Tuiuan from this research is to find out the causative factor and how the perpetrator's criminal responsibility.  As for the problem in this research are, what are the factors that led to the Criminal Act Committing 672 Pid B2020 PN Tjk?  How is the criminal responsibility of the perpetrator involved and exchanging extortion with threats?  The research method used in writing the Jumal of this research is a nomative juridical approach and an empirical approach. Based on the results of the research, the factors that cause perpetrators to commit extortion crimes with threats include economic factors, environmental factors and the third factor.  Where the role of the perpetrator is concerned, how the perpetrator does it, the weight of the mitigation side, the facts of the trial. so the perpetrator is responsible for his actions with a criminal sanction of imprisonment.